Implementasi Instalasi Pengolahan Air Limbah (IPAL) Untuk Mengatasi Pencemaran di Kantin Warung NKRI UPN “Veteran” Jawa Timur - Nisa, Diana Aqidatun; Novembrianto, Rizka; Gunawan, Rizal; Shanty, Dina Kurnia; Aulia, Salsabila (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2025)
Universitas Pembangunan Nasional "Veteran" Jawa Timur (UPNVJT) is committed to realizing a sustainable campus. However, this commitment was challenged at the Warung NKRI canteen, where liquid waste was discharged into open sewers, causing pollution and odor. This Community Service Program aimed to solve this issue through a multidisciplinary approach. The methods included educating vendors and customers on waste management and implementing a Wastewater Treatment Plant (WWTP/IPAL). To ensure sustainability, socialization on system maintenance was conducted for the Business Management Unit (BPU) and cleaning service staff. The results showed increased awareness within the canteen community and the WWTP's success in producing clearer, odorless effluent. This program proves that cross-disciplinary collaboration can deliver tangible and sustainable solutions for campus environmental sanitation.